Revisiting the Determination of the Valence Band Maximum and Defect Formation in Halide Perovskites for Solar Cells: Insights from Highly Sensitive Near-UV Photoemission Spectroscopy - Menzel D. (2021)
The authors acknowledge funding from the Federal Ministry of Education and Research (BMBF) for funding of the Young Investigator Group Perovskite Tandem Solar Cells within the program “Materialforschung für die Energiewende” (grant no. 03SF0540), the Helmholtz Association within the HySPRINT Innovation lab project, and the HyPerCells joint Graduate School. This research was supported by the joint agreement between the DAAD (German Academic Exchange Service) and FONDECYT (National Fund for Scientific, Technological Development and Technological Innovation) under the agreements 57508544 DAAD and 423-2019-FONDECYT. Further support has been provided by the PUCP vice chancellorship for research (VRI, project no. CAP-2019-3-0041/702). The authors thank Thomas Lußky for technical support, Bor Li for part of the sample preparation, and Norbert Koch, David Cahen, Isaac Balberg and Norbert Nickel for fruitful discussions. I.L. thanks the PEROSEED project and AiF project (ZIM-KK5085302DF0) for financial support.